Culture and student achievement: The intertwined roles of patience and risk-taking - Eric Alan Hanushek; Lavinia Kinne; Philipp Lergetporer; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
Patience and risk-taking - two cultural traits that steer intertemporal decision-making - are fundamental to human capital investment decisions. To understand how they contribute to international differences in student achievement, we combine PISA tests with the Global Preference Survey. We find that opposing effects of patience (positive) and risk-taking (negative) together account for two-thirds of the cross-country variation in student achievement. In an identification strategy addressing unobserved residence-country features, we find similar results when assigning migrant students their country-of-origin cultural traits in models with residence-country fixed effects. Associations of culture with family and school inputs suggest that both may act as channels.
Keywords: I21; Z10; 330; culture; patience; risk-taking; preferences; intertemporal decision-making; international student achievement; PISA